UPAYA MENINGKATKAN MOTIVASI SISWA LAKI-LAKI DALAM MEMPELAJARI TARI MINANG PADA SISWA MTsN BUNGUS TELUK KABUNG - Hendri Yanti; Fuji Astuti; Zora Iriani (FBS Universitas Negeri Padang, 2013)
Abstract The purpose of this research is to know what the efforts of teacherto motivate boys in Class VII.1 are. This research was qualitative research by using descriptive analysis method. It is described a particular situation. The instrument of the research was a researcher itself. The meeting for teaching and learning process was 5 times where the material that is delivered organizely. The result of the research described boys were interested to learn Minang dance. It can be seen from their high attention, discipline and responsibility during teaching and learning process. The teacher did individual approach by giving reward to boys who had done perfectly in dancing. This research is hoped to give contribution for others especially for art teachers. Keywords: Motivation, Students, Traditional Dance, and Indang Dance